Perspectivas atuais de jovens solteiros sobre o casamento - Carvalho, Tácio Sales (2019)
The objectives of this research are to identify the prospects for the marriage of 200 university students, five Brazilian regions and three countries of the world, to understand the feelings and strategies regarding the current state of conjugated relations and to analyze their results from the theory of stress. . She participated in the teaching research of a confessional university, with ages ranging from 18 to 34 years old, with an average age of 21 years old. Through the application of a semi-structured questionnaire, six topics related to the study were collected. The results obtained through this investigation demonstrate a conservative profile of investigated, with traditional perceptions about social interactions, a greater desire of men for conjugality and fatherhood, when reproduced as women, a dominance of beliefs and feelings in relation to current love relationships, being presence of moral distress and use of mechanisms to cope with emotions, a prevalence among them